On the estimation of the number of acoustic wideband sources using eigen-beam processing for circular apertures - Teutsch, Heinz; Kellermann, Walter (2005 IEEE Workshop on Applications of Signal Processing to Audio and Acoustics, 2005)
This paper addresses the problem of determining the number of wideband sources in an acoustic wave field. By using eigen-beam processing based on circular apertures, this method takes the physics of wave propagation into account. The eigen-beam method decomposes the sound field into eigen-solutions of the acoustic wave equation. This idea is in contrast to existing techniques that are mainly based on examining the eigenvalues of the covariance matrix estimated from measurements of an array of sensors. It is shown that by re-synthesizing these eigen-solutions, a method can be derived that is capable of adaptively estimating the number of acoustic sources in real acoustic environments. © 2005 IEEE.